Home-based nurturing care practices for children under five with low socioeconomic position in Santo Domingo, Dominican Republic - Adrianne Katrina Nelson; Laura Sánchez-Vincitore; Melanie Patricia Frias; Michelle Marie Susana; Carl Kendall; Katherine Theall; Martha Vibbert; Heidi Luft; Arachu Castro (PLoS ONE, 2025)
Background In the Dominican Republic about 14.5% of children do not reach their full potential by age five, with children of low socioeconomic position most affected. The Nurturing Care Framework is an evidence-informed actionable framework to help children thrive, but we must first understand cultural contexts and childrearing practices that contribute to delay. This study applies the Nurturing Care Framework to explore the context of home-based care among young children in the Dominican Republic. Methods We conducted a sociodemographic survey and semi-structured qualitative interview with 25 mothers ages 19–42 (7 under the age of 18 at first birth) with low socioeconomic position and children under five that live in the capital city Santo Domingo. We asked in-depth questions about the Nurturing Care Framework’s domains of responsive caregiving and opportunities for early learning. We used consensual coding and deductive thematic analysis to analyze transcriptions, examined convergence and divergence in themes between adolescent and adult mothers, and organized themes using concept mapping. Results A few mothers provide responsive caregiving to their child, but they are unaware of its benefit to their child’s development. Adolescent mothers expressed lower confidence in their mothering skills. Across age groups, mothers did not see themselves as agents of change in their child’s early learning process and allow several hours of videos each day. Mothers provide children opportunities for learning through social interaction, a possible strength among this population. With regards to security and safety, about half of mothers use corporal punishment, all but one of these is an adolescent mother. Conclusion Findings highlight the need for parenting programs that build on strengths such as child-to-child social interaction and provide parents with opportunities to develop knowledge and skills to provide early learning opportunities. Interventions should target families with low socioeconomic position and adolescent mothers.